PENGARUH GOOD CORPORATE GOVERNANCE, INVESTMENT OPPORTUNITY SET, DAN LEVERAGE TERHADAP KUALITAS LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Fachri Arifin SE (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to examine the effect of Good Corporate Governance, Investment Opportunity Set and Leverage on earnings quality. Study on manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. The sampling technique in this study used purposive sampling and obtained a number of 14 companies as research samples. The analytical method used is multiple regression analysis with a significance level of 5% which was previously performed classic assumption tests, t test statistics and coefficient of determination test (R2). The results of the study indicate that the variable of Good Corporate Governance which is proxied by institutional ownership and managerial ownership has a positive and significant effect on earnings quality. The variable of good corporate governance proxied by the audit committee has no significant effect on earnings quality. The Investment Opportunity Set variable has a positive and significant effect on earnings quality. The leverage variable has a significant negative effect on the earnings quality. The results of this study also obtained the results of the coefficient of determination test of 31.1%, while the remaining 68.9% is explained by variables outside this study.Keywords: Good Corporate Governance, Investment Opportunity Set, Leverage